Leadership and digital transformation in the South African retail banking sector - Mutwa, Larry (My University, 2021)
The purpose of this study was to explore the role of leaders in embedding a Digital transformation culture within the South African retail banking sector. With a high degree of digital disruptors rapidly penetrating the market space across all industries, business successes are more likely to be attained by those that equip their workforce with digital skills and embrace a culture of digital transformation. Therefore, good leadership is required to effectively embed a culture of digital transformation within the banking sector. Face to face semi-structured interviews conducted with senior managers in the organisations served as the primary source of data collection. The interviews were recorded and transcribed for analysis. Publicly available documents and observations of the context provided secondary data sources. The findings of the study show that awareness and organisational learning are critical in the communication and creation of a common and shared understanding of a digital transformation culture and expected behaviour. The leadership reinforces the awareness message for desired behaviour by being exemplary in living out the values through their leadership style. Organisations have a well-formed compliance culture for risk mitigation. Due to the qualitative nature of this study, the results of this study can be used to highlight the key roles of leaders in embedding a digital transformation culture and in evaluating and creating awareness on the risks associated with the failures of embedding a digital transformation culture
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Digital Business), 2021